Improving the statistical competence and collaborative skills of preservice teachers through learning by teaching and project-based learning - Poonputta, Apantee; Sarnkong, Rattikan (International Journal of Innovative Research and Scientific Studies, 2024)
The purpose of the current study was to investigate the impact of an integrated approach, combining Learning by Teaching (LbT) and Project-Based Learning (PBL), on the statistical knowledge, attitudes, and collaborative abilities of preservice teachers in the Thai educational context. The research, which was designed as a one-group experimental study, involved a sample of 27 preservice teachers from the Faculty of Education at Mahsarakham University in Thailand. We conducted participant selection using cluster random sampling. The study employed a set of instruments, including: 1) an LbT-PBL integrated learning management plan, 2) a collaborative skill evaluation form, 3) a statistical skill evaluation form, and 4) a statistical attitude evaluation form. Descriptive statistics and a one-sample t-test were employed for data analysis, utilizing a predefined criterion of 80. The findings indicate the enhancement of statistical knowledge and attitudes as well as collaborative skills among participants through the integrated LbT and PBL approaches. This empirical support confirms the success of the integrated model in advancing statistical competence and collaborative skills, especially in the context of teacher education. The positive impact on statistical knowledge and collaborative abilities highlights its potential to shape future pedagogical practices, underscoring the significance of this innovative approach in enhancing the skillset of preservice teachers.